MANAJEMEN STRATEGIK PENGEMBANGAN PARIWISATA HALAL BERKELANJUTAN: KONSEP DAN IMPLEMENTASI TERHADAP MINAT DIGITAL ENTREPRENEURSHIP MAHASISWA - Peristiwo, Hadi; Mubarok, Khamdi (Universitas Mathla’ul Anwar Banten, 2025)
Halal tourism and digital entrepreneurship require an appropriate strategic management approach as an effort to create a sustainable halal tourism and digital entrepreneurial world. Strategic planning for a halal tourism destination is a key word in increasing the competitiveness of the halal tourism sector and the need for digitalization in developing this sector. The aim of this research is to analyze the potential of halal tourism in relation to digital entrepreneurship, as well as determine the implementation of existing and potential strategic management and determine the implementation of the quality of planning, implementation, assessment and follow-up strategic planning which is in accordance with the standards and quality of sustainable halal tourism in relation to student digital entrepreneurship. This research is a type of qualitative research. The research results show that appropriate strategic management can improve existing, potential and sustainable halal tourism supported by digital entrepreneurship.